Effective Commuity Response to Disaster: A Community Approach to Disaster Preparedness and Response - Mark A. Brennan (EDIS)
FCS9254, a 4-page fact sheet by M.A. Brennan, is part of a series of discussions on the impact of community action in response to natural and other disasters. This fact sheet identifies and suggests methods for linking local organizations, recruiting volunteers, and implementing coordinated action plans prior to, and after, the impact of natural disasters. Includes references, suggested reading, and links to useful Web sites. Published by the UF Department of Family Youth and Community Sciences, July 2006.